Warming enhances sedimentation and decomposition of organic carbon in shallow macrophyte‐dominated systems with zero net effect on carbon burial. (17th August 2018) - Velthuis, Mandy; Kosten, Sarian; Aben, Ralf; Kazanjian, Garabet; Hilt, Sabine; Peeters, Edwin T. H. M.; van Donk, Ellen; Bakker, Elisabeth S.
Abstract: Temperatures have been rising throughout recent decades and are predicted to rise further in the coming century. Global warming affects carbon cycling in freshwater ecosystems, which both emit and bury substantial amounts of carbon on a global scale. Currently, most studies focus on the effect of warming on overall carbon emissions from freshwater ecosystems, while net effects on carbon budgets may strongly depend on burial in sediments. Here, we tested whether year‐round warming increases the production, sedimentation, or decomposition of particulate organic carbon and eventually alters the carbon burial in a typical shallow freshwater system. We performed an indoor experiment in eight mesocosms dominated by the common submerged aquatic plant Myriophyllum spicatum testing two temperature treatments: a temperate seasonal temperature control and a warmed (+4°C) treatment ( n  = 4). During a full experimental year, the carbon stock in plant biomass, dissolved organic carbon in the water column, sedimented organic matter, and decomposition of plant detritus were measured. Our results showed that year‐round warming nearly doubled the final carbon stock in plant biomass from 6.9 ± 1.1 g C in the control treatment to 12.8 ± 0.6 g C (mean ±  SE ), mainly due to a prolonged growing season in autumn. DOC concentrations did not differ between the treatments, but organic carbon sedimentation increased by 60% from 96 ± 9.6 to 152 ± 16 g C m −2  yaer −1 (mean ±  SE ) from control to warm treatments. Enhanced decomposition of plant detritus in the warm treatment, however, compensated for the increased sedimentation. As a result, net carbon burial was 40 ± 5.7 g C m −2  year −1 in both temperature treatments when fluxes were combined into a carbon budget model. These results indicate that warming can increase the turnover of organic carbon in shallow macrophyte‐dominated systems, while not necessarily affecting net carbon burial on a system scale. Abstract : Global warming affects carbon cycling in freshwater ecosystems, which both emit and bury substantial amounts of carbon. Most studies focus on the effect of warming on overall carbon emissions, while net effects on carbon budgets may strongly depend on burial in sediments. We showed that year‐round warming in a shallow macrophyte‐dominated mesocosm experiment doubled the carbon stock in plant biomass, increased sedimentation, and enhanced decomposition of plant detritus. These enhanced carbon fluxes compensated each other so that burial remained similar between treatments. This indicates that warming can increase the turnover of organic carbon, while not necessarily affecting net carbon burial.